Application of the Point Stress Criterion to Assess the Bond Strength of a Single-Lap Joint - Sajikumar, K.S.; Asok Kumar, N.; Nageswara Rao, B. (Проблемы прочности, 2014)
Finite element analysis has been carried out to obtain the interfacial stresses in a single lap joint using a special 6-node isoparametric element for adhesive layer. The analysis results are found to be in good agreement with the closedform solution of Goland and Reissner. The peak normal and shear stresses found in the adhesive layer at the edges of the joint are due to stress singularity. The bond strength of the single-lap joint is estimated considering one of the stress fracture criteria known as the point stress criterion. Bond strength estimates are found to be reasonably in good agreement with existing test results. Выполнен конечноэлементный расчет напряжений в зоне соединения внахлестку с использованием в адгезионном слое специальных 6-узловых изопараметрических конечных элементов. Результаты расчета хорошо согласуются с решениями, полученными в замкнутом виде Голандом и Рейсснером. Показано, что максимальные нормальные и касательные напряжения в адгезионном слое имеют место в торцах соединения, что обусловлено их сингулярностью. Оценена адгезионная прочность соединения внахлестку с помощью критерия прочности, известного как критерий точечных напряжений. Расчетные значения адгезионной прочности тесно коррелируют с известными экспериментальными данными. Проведено скінченноелементний розрахунок напружень у зоні з єднання внапуск із використанням у адгезійному шарі спеціальних 6-вузлових ізопараметричних скінченних елементів. Результати розрахунку добре узгоджуються з розв язками, отриманими у замкненому вигляді Голандом і Рейсснером. Показано, що максимальні нормальні і дотичні напруження в адгезійному шарі мають місце в торцях з єднання, що зумовлено їх сингулярністю. Оцінено адгезійну міцність з єднання внапуск за допомогою критерію міцності, відомого як критерій точкового напруження. Розрахунки і значення адгезійної міцності тісно корелюють із відомими експериментальними даними.